How the Ghosts Stole All the Kisses: Slow Modernity. (December 2017) - Wilkinson, Alex
We are getting faster, or so we have been led to believe. Planes, trains, and automobiles—alongside the substrates of online modernity—have seemed to suggest to us that the world is a place we are constantly in need of catching up with. In turn, partially in response to institutional demands on productivity, some academics have suggested slow methods in research. 1 Yet, what if we were never fast in the first place? What if the things and atmospheres of Western industrial modernity actually produce slow ontologies of feeling as we traverse space and place? Straddling history, literature, and (auto)ethnographic attunements to emotions and society, this article attempts to suggest there is a modernity which is slow—an "endless mastication"—in which we, as both subject and subjects, are chewed-up and spat out amid the endlessly deferring signs of the presence and absence of meaning in social space.